The Influence of Social and Economic Factors of Entrepreneurs on SMEs in West Java - Siti Marti’ah; Berta Dian Theodora (International Conference on Multidisciplinary Research, 2022)
The population of entrepreneurs in Indonesia has increased from 1.6% to 3.47%. The number of women who work in the field of entrepreneurship is now 2.4 times more than men although the businesses for women tend to be smaller and grow more slowly than those for men. There are some constraints causing women to be reluctant to practice entrepreneurship, such as limited information, lack of profiles to imitate, limited access to business finance, lack of experience in doing business, and a low level of confidence to start and develop a business. Low level of education and ideological barriers of women related to the household, known as the "triple burden of women", are also among the constraints. The independent variables of this research were social condition variables (X1 ) and economic conditions (X2 ) while the dependent one was the number of Small and Medium Entrepreneurs (SMEs) (Y). The research population was the social and economic conditions and the number of SMEs from 27 districts of West Java. The samples were limited to only the data from 2016 – 2020 (5 years). The data analysis technique used for this research was panel data regression analysis. The results show that social and economic conditions have a positive and significant impact on the number of SMEs in 27 districts in West Java with an R 2 2 score of 99%. Keywords: SMEs, Social Factor, Economic, Panel Data, West Java